Role of plaque calcification regulators osteoprotegerin and matrix Gla-proteins in stable angina and acute myocardial infarction. Issue 3 (March 2015) - Margonato, Alberto; Gorla, Riccardo; Macchi, Andrea; Buzzetti, Fabio; Franzoni, Irene; Pedrigi, Maria Cristina; Rosa, Isabella; Sirtori, Marcella; Villa, Isabella; Rubinacci, Alessandro
<x xml:space="preserve">Abstract</x> Aim To assess serum levels of the plaque calcification regulators osteoprotegerin (OPG) and Matrix Gla-proteins (MGP) in individuals with stable angina and acute myocardial infarction submitted to coronary angiography and their relation to coronary artery disease burden. Methods The study included 40 individuals affected by ST-elevation myocardial infarction (STEMI) and 40 individuals with stable angina who all underwent coronary angiography, with evaluation of the extent of coronary artery disease by Syntax Score calculation and measurement of serum OPG and MGP levels. Osteoporosis was excluded by femoral and vertebral computerized bone mineralometry. Results Serum OPG and MGP levels were respectively 3.87 ± 1.07 pmol/l and 6.80 ± 2.43 nmol/l in the stable angina group, 7.57 ± 1.5 pmol/l and 7.18 ± 1.93 nmol/l in the STEMI group (P < 0.01 and P = 0.33, respectively). Pearson correlation coefficient for OPG and Syntax Score, MGP and Syntax score was respectively 0.79 (P < 0.01) and 0.18 (P = 0.22) in the stable angina group, −0.03 (P = 0.43) and 0.10 (P = 0.5) in the STEMI group. Serum OPG and MGP levels were respectively 5.52 ± 1.02 pmol/l and 7.56 ± 1.42 nmol/l in diabetics, 4.3 ± 0.8 pmol/l and 6.52 ± 1.14 nmol/l in nondiabetics (P < 0.05; P < 0.05). Conclusion OPG, in a relatively small group of patients with stable angina, correlates proportionally with the extent of coronary artery disease (CAD), as evaluated by the Syntax Score. Higher serum OPG levels can be observed in individuals with STEMI regardless of CAD burden. As for MGP, a potential role as marker of plaque calcification remains unproven.